Globalization and the Transformation of Indigenous Morality: A Philosophical Study of the Yoruba Concept of Omoluabi - Adewale Motadegbe; Sheriff Olasunkanmi IBIYEMI (ABUAD Journal of the Humanities-AGIDIGBO, 2025)
Even as globalization has, no doubt, catalyzed or served as a basis for advancements in several spheres of human endeavours across the globe, it is also pertinent to highlight or indicate some of its drawbacks, especially as it pertains to the preservation of culture and morality. Whereas some studies have already attested to the fundamental link between culture and morality, some others have moved on to indicate how globalization may have a negative impact on culture and morality, especially within the African context. The present research queues with the latter group of studies as it investigates the extent to which the moral and cultural values associated with the Yoruba concept of Omoluabi has metamorphosed in the 21st century. The research relies on philosophical and hermeneutical analyses for its agenda as it discloses how the concept of ‘Omoluabi’, has evolved from its original usage and semantics to what now obtains in the 21st century.